2022
DOI: 10.3389/fnmol.2022.920221
|View full text |Cite
|
Sign up to set email alerts
|

Multi-mtDNA Variants May Be a Factor Contributing to Mitochondrial Function Variety in the Skin-Derived Fibroblasts of Leber's Hereditary Optic Neuropathy Patients

Abstract: Heterogeneity is a major feature of Leber's hereditary optic neuropathy (LHON) and has a significant impact on the manifestation and diagnosis of the disease. This study explored whether multiple variations in mitochondrial genes were associated with the heterogeneity, mainly phenotypic heterogeneity. Ophthalmic examinations were conducted in two probands with LHON with G11778A and multiple mitochondrial DNA gene (mtDNA) variants. Skin fibroblast cell lines were generated from patients and age- and sex-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Although fibroblasts cannot used for the study of axon degeneration and neural signaling, multiple studies demonstrated that they can be used as a valuable strategy for studying mitochondrial impairment in neurological disorders ( Olesen et al, 2022 ). In addition, our previous study ( Yao et al, 2022 ) and the current manuscript have proved that fibroblasts could reflect some cellular phenotypes of RGC cells with LHON, such as energy metabolism, mitochondrial dysfunction, and oxidative stress, which was consistent with iPSC. Therefore, in this study, we conducted LHON patients’ skin derived fibroblasts for the study of mitochondria function and inflammation.…”
Section: Discussionsupporting
confidence: 84%
“…Although fibroblasts cannot used for the study of axon degeneration and neural signaling, multiple studies demonstrated that they can be used as a valuable strategy for studying mitochondrial impairment in neurological disorders ( Olesen et al, 2022 ). In addition, our previous study ( Yao et al, 2022 ) and the current manuscript have proved that fibroblasts could reflect some cellular phenotypes of RGC cells with LHON, such as energy metabolism, mitochondrial dysfunction, and oxidative stress, which was consistent with iPSC. Therefore, in this study, we conducted LHON patients’ skin derived fibroblasts for the study of mitochondria function and inflammation.…”
Section: Discussionsupporting
confidence: 84%
“…Multiple studies indicated the derived fibroblasts as a valuable strategy for studying mitochondrial damage in neurological disorders, such as AD (Alzheimer’s Disease) [ 45 , 46 ], PD (Parkinson’s disease) [ 47 , 48 ], HD (Huntington’s disease) [ 49 , 50 ] and ALS (amyotrophic laternal sclerosis) [ 51 , 52 ]. Our previous studies also found mitochondrial dysfunction, respiration disorder and decreased cell viability in patients’ fibroblasts with m.G11778A [ 16 ]. Thus, to some extent, fibroblasts can stimulate the pathological process and can be used as an alternative model to explore molecular changes.…”
Section: Discussionmentioning
confidence: 63%
“…Finally, they were diagnosed as LHON bearing m.G11778A. Detailed information can be found in a previous article [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a PVDF membrane was exposed to enhanced chemiluminescence using a chemiluminescence apparatus (GelView6000Plus, Guangzhou Biolight Biotechnology, Guangzhou, China). 20 , 22 …”
Section: Methodsmentioning
confidence: 99%